2020
DOI: 10.3174/ajnr.a6905
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Technical and Adjunctive Factors with Quantitative Tumor Reduction in Children Undergoing Selective Ophthalmic Artery Infusion Chemotherapy for Retinoblastoma

Abstract: BACKGROUND AND PURPOSE: Selective ophthalmic artery infusion chemotherapy has improved ocular outcomes in children with retinoblastoma. Our aim was to correlate quantitative tumor reduction and dichotomous therapeutic response with technical and adjunctive factors during selective ophthalmic artery infusion chemotherapy for retinoblastoma. An understanding of such factors may improve therapeutic efficacy. MATERIALS AND METHODS:All patients with retinoblastoma treated by selective ophthalmic artery infusion che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…40,41 Moreover, the nebulous effect of operator experience and collaboration among the multidisciplinary team, in addition to a relative lack of literature concerning technical factors promoting efficacy, lead to global disparities in management approach and knowledge. 37 The greatest Rb burden falls on lower and lower middle-income countries where realistic goals in improving survival and eye preservation typically focus on increasing screening of children with familial Rb, retaining families in the healthcare system, and promoting treatment adherence. 42 In some middle-and high-income countries (representing approximately 53% of new cases annually), 43 eye-preserving strategies have been increasingly used, though related adverse effects, comorbidities, and historically lower ocular salvage for more advanced eyes (groups D and E) leave room for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…40,41 Moreover, the nebulous effect of operator experience and collaboration among the multidisciplinary team, in addition to a relative lack of literature concerning technical factors promoting efficacy, lead to global disparities in management approach and knowledge. 37 The greatest Rb burden falls on lower and lower middle-income countries where realistic goals in improving survival and eye preservation typically focus on increasing screening of children with familial Rb, retaining families in the healthcare system, and promoting treatment adherence. 42 In some middle-and high-income countries (representing approximately 53% of new cases annually), 43 eye-preserving strategies have been increasingly used, though related adverse effects, comorbidities, and historically lower ocular salvage for more advanced eyes (groups D and E) leave room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…56,57 We have previously reported that TBO of the ECA is a safe and effective method for optimizing ocular hemodynamics with the intended effect of increasing treatment response. 31,37 Others have reported successful application of the bIAC technique. 58 Alternately, reports have described the use of cyanoacrylate-based embolization of ECA collaterals, 59 or selective occlusion of the middle meningeal artery to modulate ocular circulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations